The Effect of Performance Allowances on Work Motivation and Employee Performance at the Ministry of Religion of Bengkulu City - Zoniarti Zoniarti; Ramadan Subhi (Penerbit Jurnal Indonesia, 2024)
This study aims to analyze the effect of performance allowances on work motivation and employee performance at the Ministry of Religion (Kemenag) of Bengkulu City. this uses quantitative method as an explanatory research approach, the data analysis technique used is multiple regression. The statistical test results show that there is a positive and significant influence between performance allowances and employee work motivation, as well as between performance allowances and employee performance. The analysis also identified several potential problems related to the provision of performance allowances, including unclear criteria, unequal distribution, and delays in payment. To address these issues, it is recommended that performance allowance policies be clear, transparent, and involve employees in program planning and evaluation. The importance of effective and open communication in managing performance benefits is also emphasized. The general benefits of performance allowances, such as high motivation, increased productivity, and improved psychological well-being of employees, were positively highlighted in this study. With the results of calculations using SPSS, it was found that work motivation and performance variables jointly significantly affect employee performance allowances. The test results state the rejection of the null hypothesis, indicating that the higher the value of performance allowance, the higher the work motivation and performance of employees of the Ministry of Religious Affairs of Bengkulu City.